Deontic Logic in Computer Science - van der Meyden, Ron (Springer, 2017)
This volume presents the papers contributed to ?EON 2008, the 9th Inter- tional Conference on Deontic Logic in Computer Science, held in Luxembourg, July 16–18, 2008. This biennial conference series is designed to promote int- national cooperation amongst scholars who are interested in deontic logic and its use in computer science. The scope of the conference is interdisciplinary, and includes research that links the formal-logical study of normative concepts and normative systems with computer science, arti?cial intelligence, philosophy, - ganization theory, and law. The ?EON website, http://www.deonticlogic.org, contains links to previous conferences and their papers. This history reveals a vibrant interdisciplinary research program. Papers for these conferences might address such general themes as the - velopment of formal systems of deontic logic and related areas of logic, such as logics of action and agency, or the formal analysis of all sorts of normative concepts, such as the notions of rule, role, regulation, authority, power, rights, responsibility, etc., or the formal representation of legal knowledge. They might also be concerned with applications, such as the formal speci?cation of n- mative multiagent systems, the speci?cation of systems for the management of bureaucratic processes in public or private administration, or the speci?cation of database integrity constraints or computer security protocols, and more. Of particular interest is the interaction between computer systems and their users.